2020
DOI: 10.1177/2399808320930247
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between urban development patterns and noise complaints in England

Abstract: The role of urban planning in sound environments has recently received increased research attention. This study aims to examine the relationship between the rate of noise complaints and urban development patterns concerning planning and landscape at city/region level. Open-source government data sets are used for statistical analysis across all district and unitary local authorities in England. The indicators for urban development patterns are categorised into six groups: population, industrial structure, buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It is important to get such information at city scale because it will reflect trends in reaction to environmental noise from the population, e.g., through noise complaints; indeed, recent research in UK cities has shown that noise complaints patterns will vary depending on urban structure and population factors: noise complaints are likely to be higher in service-oriented cities with high population densities; large and clustered cities also have a higher prevalence of noise complaints compared to others, while fragmented cities are likely to have less noise complaints [10]. Nevertheless, while relevant from a noise exposure and public health perspective, the indicators used for noise maps are not necessarily representative of noticeable changes in the acoustic environment at specific locations.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to get such information at city scale because it will reflect trends in reaction to environmental noise from the population, e.g., through noise complaints; indeed, recent research in UK cities has shown that noise complaints patterns will vary depending on urban structure and population factors: noise complaints are likely to be higher in service-oriented cities with high population densities; large and clustered cities also have a higher prevalence of noise complaints compared to others, while fragmented cities are likely to have less noise complaints [10]. Nevertheless, while relevant from a noise exposure and public health perspective, the indicators used for noise maps are not necessarily representative of noticeable changes in the acoustic environment at specific locations.…”
Section: Introductionmentioning
confidence: 99%
“…A study in London observed a spatially heterogeneous noise reduction ranging from 1.2 to 10.7 dB [ 23 ]. This is not surprising, as noise levels in cities are determined by not only the amount of traffic, but also by urban morphology (e.g., land use, traffic network design, building layout and façade orientation, and green space ratio) [ 24 , 25 , 26 ]. Traffic flow composition was also altered.…”
Section: Introductionmentioning
confidence: 99%
“…Road traffic noise, as the primary urban noise source and the most annoying sound source, has a pronounced effect on residents, particularly those living in roadside highrise buildings, due to their compact urban form (Brown et al, 2015;Tong and Kang, 2021). The built environment could modify the relationship between noise exposure and self-reported responses to noise, related to the wider determinants of health (Peris and Fenech, 2020).…”
Section: Introductionmentioning
confidence: 99%